Measuring the impact of out-of-class communication through instant messaging - Nkhoma, Clara Akuzike; Thomas, Susan; Nkhoma, Mathews Zanda; Sriratanaviriyakul, Narumon; Truong, Trang Huyen; Vo, Hung Xuan (Education & training (London), 2018)
Purpose Despite the growing body of literature demonstrating the role of communication in educational settings, there are limited up-to-date studies exploring the use of an instant messaging (IM) tool and its impacts on students’ learning outcomes, especially in the tertiary education in Vietnam. This study approached IM as an out-of-class communication (OCC) approach in computer-mediated communication. The purpose of this paper is to investigate students’ perceived quality of information received and its influence on their perceived performance proficiency as a result of their lecturers’ clarification of their enquiries through an online instant message application, namely Remind (www.remind.com/). Design/methodology/approach The target groups were first-year business students in an international university in Vietnam. The analysis of the data gathered from the questionnaire was carried out using a measurement model and a structural equation model. Findings The findings indicate that using OCC technology creates social bonding between students and lecturers by allowing students to clarify the ambiguity of concepts learnt in class and create a sense of connection with their lecturers which leads to better student engagement and hence improved learning outcomes. Originality/value The authors highlight the evidence of effective usage of IM tool by university students as a meaningful communication tool and the need to integrate technology into all educational settings.